AUTORÍA, MUTACIONES Y MIGRACIONES. PRESENCIAS DE CINEASTAS ESPAÑOLES EN EL MUSEO: ALBERT SERRA - Dra. Laura GÓMEZ VAQUERO (Fonseca, Journal of Communication, 2023)
One of the places that, for more than a decade, has been a means not only of exhibition but also of financing projects arising from Spanish filmmakers whose work finds it difficult to fit into conventional cinemas is the museum and the exhibition halls. This migration of filmmakers to the museum is due to the crisis afflicting the film industry, especially in Spain.